Internalisasi Maqasid Al-Syari'ah dalam Proses Nikah Adat Bugis - Rosmayanti; Nawas, Zuhri Abu; Assaad, A. Sukmawati; Takdir; Arif, Firman Muhammad; Mustafa, Adriana (Palita: Journal of Social Religion Research, 2024)
The research explains the internalization of Maqasid Al-syari’ah in the Bugis traditional marriage process, because of various oblique views of Bugis marriage customs, it should be addressed wisely and wisely. This research is qualitative research using an Islamic legal juridical approach with qualitative descriptive analysis.  Data sources are primary data conducted through interviews with traditional leaders, religious leaders, community leaders, and secondary data taken from documents that have relevance to the research. Data collection techniques are observation, interviews, and documentation. The results showed that the meaning of the panai money marriage tradition, although not found in Islamic law, is not contrary to sharia and does not damage the faith. Because in it there is benefit, both for the wife and the husband. This kind of custom is called al-adah aṣ-ṣaḥiḥ or al-urf aṣ-ṣaḥiḥ, which is a good custom that can be used as a legal consideration. Islam as a merciful religion accepts customs and culture as long as they do not contradict Islamic shari'a and the custom has become a provision that must be implemented and is considered a rule that must be obeyed, then the custom can be used as a foothold as Islamic law recognizes the validity of customs in the interpretation of law, as the fiqhiyyah rule: al-adah muhakkamah which means that custom can be used as a legal footing. Keywords: Philosophical, Bugis Custom, Maqasid Al-Syari’ah